Identification and management of a novel Danshen leaf anthracnose caused by Colletotrichum karstii in Salvia miltiorrhiza Bunge in China - Ma, Haoyue; Huang, Liguo; Guo, Lulu; Chen, Shan; Liu, Jiale; Liu, Changyun; Dou, Yanxia; Sun, Xianchao; He, Lin; Ma, Guanhua (Frontiers in Plant Science, 2025)
Danshen (Salvia miltiorrhiza Bunge), a member of the genus Salvia within the Lamiaceae family, holds significant economic and medicinal value. Regrettably, the emergence of a novel leaf anthracnose in 2020 has significantly impacted its cultivation, leading to decreased yield and compromised quality. This newly identified pathogen was meticulously isolated from affected leaves, employing meticulous single conidia isolation techniques. Subsequent confirmation of pathogenicity was achieved through strict adherence of Koch’s postulates. To ensure precise identification, morphological characteristics were supplemented with tandem sequence analysis targeting the rDNA internal transcribed spacer (ITS), β-tubulin (TUB), and histone (His3) regions. Combining molecular biology techniques with morphological observation and Koch’s postulates, the pathogen was conclusively identified as Colletotrichum karstii. Further investigations focused on understanding the environmental factors influencing the mycelial growth and sporulation of the pathogen. The optimum temperature for the growth of C.karstii is 25°C, the suitable light conditions are 12h light/12h dark or 24h dark, and the suitable pH is 5 to 9. Utilizing BIOLOG phenotypic analysis technique, the metabolic utilization of carbon and nitrogen sources by the pathogen was assessed across different temperatures (20°C, 25°C, and 30°C). Results indicated the highest utilization rates at 25°C, particularly for arbutin and L-tryptophan. Lastly, the efficacy of 15 chemical fungicides and six botanical fungiticide against C. karstii was evaluated in vitro, revealing fluazinam as the most potent inhibitor against mycelial growth with EC50 of 0.0725 mg/mL for mycelium and 0.0378 mg/mL for spore germination, respectively. The 1 % osthole emulsion in water was found to have the strongest inhibitory effect on the growth of mycelium, with an EC50 value of 4.8984 µg/mL. Spore germination was most strongly inhibited by the 80 % ethylicin EC, which had an EC50 value of 0.5541 µg/mL. This study represents the first documentation of C. karstii as a causative agent of anthrax in Danshen, underscoring the significance of these findings for agricultural management and disease control strategies.